PENELITIAN TENTANG KOMPETENSI KEPRIBADIAN GURU DALAMMENERAPKAN PENDIDIKAN KARAKTER DISIPLIN - Muawanah; Trian Pamungkas Alamsyah; Nana Hendracipta (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the teacher's personality competence in implementing discipline character education for fifth-grade students. The study described in this article was qualitative descriptive research and the subjects of the research were teachers and students. The study involved the fifth-grade students at the Khalifah Islamic Elementary School in Serang in the 2020/2021 academic year. Data collection was carried out by means of observation, interviews and supported by documentation. Data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of this study could be concluded that (1) the teacher at class V of Abdullah bin Mas'ud Islamic Elementary School Khalifah Serang has implemented personality competencies in learning. The personality competency shown by the teacher was the personality of teachers who have noble character and exemplary for students. (2) The ways of the teacher at class V of Abdullah bin Mas'ud understanding well about the supporting and inhibiting factors in implementing disciplined character education were seen from the teacher’s understanding in instilling the discipline character education, with the attitude or examplary of the teacher in providing examples of disciplined character, and then from the support from the school and the important role of parents for students. And (3) the teacher's efforts in applying the discipline character for students that have been implemented well were seen on the existence of habits such as dhuha prayer and Tilawatil Al-Qur’an, the existence ofrules or regulations during the online learning process, and the existence of exemplary that could be formed due to habits carried out by students